From Challenge to Growth: The Adaptive Journey of a Volunteer Teacher with High AQ - Yoko Jimmy Panjaitan; Myrna Anissaniwaty; Muhammad Aiman Alif Zulkifl; Rifan Adhitia Gumilar (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The teachers, particularly among volunteer teachers, faces complex challenges amid the dynamic landscape of education. In addition to teaching, they must adapt to constantly changing environments without material compensation or job security. In this context, career adaptability becomes crucial to help volunteer teachers navigate career transitions and challenges. One factor that supports career adaptability is adversity quotient (AQ). This study aims to analyze the influence of AQ on the career adaptability of volunteer teachers in Bandung. The proposed hypothesis is that adversity quotient significantly influences career adaptability. A quantitative approach was employed using a survey design with questionnaires that had been tested for validity and reliability. The research subjects were 67 volunteer teachers selected through purposive sampling. Data were analyzed using simple linear regression to examine the influence of AQ on career adaptability. The results indicate that adversity quotient has a significant effect on career adaptability (p < 0.05). These findings highlight the importance of developing adversity quotient to enhance career adaptability. This study is expected to serve as a foundation for designing intervention programs, such as resilience training and mentoring, to support the career sustainability of volunteer teachers in Indonesia.Profesi guru, khususnya guru relawan, menghadapi tantangan yang kompleks di tengah dinamika pendidikan. Selain mengajar, mereka harus beradaptasi dengan kondisi lingkungan yang terus berubah tanpa jaminan materi maupun status pekerjaan yang pasti. Dalam konteks ini, adaptabilitas karir menjadi kemampuan penting agar guru relawan mampu menghadapi transisi dan tantangan kerja. Salah satu faktor yang mendukung adaptabilitas karir adalah adversity quotient (AQ). Penelitian ini bertujuan untuk menganalisis pengaruh AQ terhadap adaptabilitas karir pada guru relawan di Kota Bandung. Hipotesis yang diajukan adalah adversity quotient berpengaruh signifikan terhadap adaptabilitas karir. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei menggunakan kuesioner yang telah diuji validitas dan reliabilitasnya. Subjek penelitian adalah 67 guru relawan yang dipilih melalui teknik purposive sampling. Analisis data dilakukan dengan regresi linier sederhana untuk menguji pengaruh adversity quotient terhadap adaptabilitas karir. Hasil penelitian menunjukkan bahwa adversity quotient memiliki pengaruh signifikan terhadap adaptabilitas karir (p < 0,05). Temuan ini menggarisbawahi pentingnya pengembangan adversity quotient untuk meningkatkan adaptabilitas karir. Penelitian ini diharapkan dapat menjadi landasan bagi pengembangan program intervensi, seperti pelatihan resiliensi dan mentoring, guna mendukung keberlanjutan karir guru relawan di Indonesia.